From flexibility to adaptive learning: a pre-COVID-19 perspective on distance education in Latin America - Miralrio, Alan; Muñoz-Villota, Jessica; Camacho-Zuñiga, Claudia (Frontiers in Computer Science, 2024)
At the time of this writing, emerging Generative Artificial Intelligence (GenAI) technologies, such as ChatGPT, Bard, and DALL-E, are shaping education. Despite their great potential for enhancing education, the discussion on the risks for the Society is an ongoing debate. Remote or distance education (DE) in developed countries has evolved in parallel to the permeation of Information and Communication Technologies (ICT). In Latin America (LATAM), a deep understanding of this interrelated evolution will encourage an efficient implementation of innovative policies, pedagogies, and technologies, including GenAI. This paper presents the historical development of DE in LATAM, drawing connections with milestones along the evolution of ICT in the region. This evolution is described across five generations: Correspondence, Audiovisual, ICTs-based, Web-based, and Interactive. Each generation offered incremental benefits to students, from flexibility and well-designed instructional materials to adaptive, interactive, and cost-effective education. This research encompassed a comprehensive search on Scopus, Web of Science, Google Scholar, ScienceDirect, Latindex, Dialnet, Redalyc, and SciELO with an historical approach. It yielded 97 peer-reviewed articles, books, and reports from recognized international organizations, published in Spanish or English and covering a period spanning from the end of the 19th century to the onset of COVID-19 lockdown. The analysis confirms the critical role of Higher Education Institutions (HEIs) in LATAM in supporting ICT integration, demonstrating a synergistic interplay with DE. Notwithstanding, the region’s social inequality and digital divide have delayed the full deployment of DE’s advantages, in comparison to USA and Europe. The paper exposes different scenarios and tech-educational requirements of DE, showcasing Mexico, Brazil, and Colombia, as well as other countries with smaller populations. Notably, by 2019, Tecnologico de Monterrey in Mexico, and Universidade de São Paulo and Universidade Federal da Paraíba in Brazil have pioneered the implementation of the Fifth Generation of DE in the region. The findings of this research highlight the value of DE as a cost-effective solution to traditional education, addressing social barriers and broadening educational access in LATAM, especially during emergencies. This research poses significant implications that can equip digital technology providers, HEIs, governments, and policymakers as they navigate the ongoing educational challenges.